Effect of Climate Change on Agricultural Output Growth in Ethiopia: Co-Integration and Vector Error Correction Model Analysis - Melaku Adinew Aytehgiza; Gebrekirstos Gebresilasie (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
This study examined the effect of climate change on agricultural output growth in Ethiopia. Co- Integration and Vector Error Correction Model estimation technique and data for the period 1981-2016 was used. Changing in annual mean temperature, annual mean rainfall, carbon dioxide emission and forest depletion were used to attribute variables for climate change. The result of vector error correction model indicate that both in the long-run and short-run, carbon dioxide emissions negatively affect agricultural output growth in Ethiopia. Annual temperature and annual rainfall negatively affect agricultural output growth in the long run and short run respectively.  On the other hand, forest depletion has positive effect on agricultural output growth both long run and the short-run respectively. Policy maker should develop policies to reduce sources of carbon dioxide emissions and introduce mitigation and adaptation measures to sustain the agricultural economic growth.